Legal Consequences and Notary Responsibilities for the Hawalah Contract Deed that Does Not Meet the Provisions of Sharia Law (Study of Decision Number 1922/pdt.g./2020/pa.btm) - Haeratun (Faculty of Law, Universitas Pekalongan, 2025)
One of the important issues in marriage law in Indonesia that seems to be endlessly discussed is the registration of marriages and divorces in The Religious Courts. This issue is still being hotly discussed not only by Islamic law experts (ulama) but also among ordinary people. The purpose of this study is first, to explain that when a woman has a husband and divorces isn’t in the Court (her marital status is recorded), when she remarries (underhands marriage) with another man and then files for marriage confirmation (itsbat nikah); second, to analyze related to a woman who divorces not in the Court with her ex-husband (underhands marriage), then she remarries (underhands marriage) with another man and then files for marriage confirmation (itsbat nikah). The research method includes, the type of doctrinal legal research. The results of this study are that the Religious Court has the authority to annul a marriage if the marriage is considered invalid (no legal force), or if a marriage is considered not to meet the requirements of a marriage that has been determined, or if the marriage that has been carried out is known to have a legal defect as a result of a lie and mistake or because of coercion. Meanwhile, the data collection technique in this study was carried out using several stages, starting with the collection of secondary data in the form of primary legal materials and secondary legal materials related to marriage registration and the problems of polyandrous marriage confirmation and its legal consequences for the children.